A novel Mcl-1 inhibitor synergizes with venetoclax to induce apoptosis in cancer cells - Tianming Zhao; Qiang He; Shurong Xie; Huien Zhan; Cheng Jiang; Shengbin Lin; Fangshu Liu; Cong Wang; Guo Chen; Hui Zeng (BMC, 2023)
Abstract Background Evading apoptosis by overexpression of anti-apoptotic Bcl-2 family proteins is a hallmark of cancer cells and the Bcl-2 selective inhibitor venetoclax is widely used in the treatment of hematologic malignancies. Mcl-1, another anti-apoptotic Bcl-2 family member, is recognized as the primary cause of resistance to venetoclax treatment. However, there is currently no Mcl-1 inhibitor approved for clinical use. Methods Paired parental and Mcl-1 knockout H1299 cells were used to screen and identify a small molecule named MI-238. Immunoprecipitation (IP) and flow cytometry assay were performed to analyze the activation of pro-apoptotic protein Bak. Annexin V staining and western blot analysis of cleaved caspase 3 were employed to measure the cell apoptosis. Mouse xenograft AML model using luciferase-expressing Molm13 cells was employed to evaluate in vivo therapeutic efficacy. Bone marrow samples from newly diagnosed AML patients were collected to evaluate the therapeutic potency. Results Here, we show that MI-238, a novel and specific Mcl-1 inhibitor, can disrupt the association of Mcl-1 with BH3-only pro-apoptotic proteins, selectively leading to apoptosis in Mcl-1 proficient cells. Moreover, MI-238 treatment also potently induces apoptosis in acute myeloid leukemia (AML) cells. Notably, the combined treatment of MI-238 with venetoclax exhibited strong synergistic anti-cancer effects in AML cells in vitro, MOLM-13 xenografts mouse model and AML patient samples. Conclusions This study identified a novel and selective Mcl-1 inhibitor MI-238 and demonstrated that the development of MI-238 provides a novel strategy to improve the outcome of venetoclax therapy in AML.